2018
DOI: 10.1074/jbc.h118.002654
|View full text |Cite
|
Sign up to set email alerts
|

New links between lipid accumulation and cancer progression

Abstract: Individuals with elevated lipid levels are at risk for developing cardiovascular disease as well as cancer. Sterol regulatory element-binding protein transcription factors (SREBPs) are inducers of lipid synthesis. Elevated SREBPs levels are linked to cell proliferation and metastasis. Using biochemical and mouse models of cancer, Zhao have discovered that nuclear SREBP-1a-dependent transcription is activated by pyruvate kinase M2 in cancer cells, which promotes tumor growth. Targeting the lipogenesis pathway m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, both AMPK and Akt are the upstream regulator of sterol regulatory element-binding protein-1 (SREBP-1) and can directly phosphorylate SREBP-1. Recently, SREBP-1, which gets upregulated in different types of cancer, has been linked to play a role in the oncogenic signaling-mediated glucose uptake and de novo lipogenesis [46][47][48]. The pharmacological targeting of SREBP-1 has revealed to significantly inhibit the glioblastoma cell growth, suggesting it as a novel molecular target in cancer [49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both AMPK and Akt are the upstream regulator of sterol regulatory element-binding protein-1 (SREBP-1) and can directly phosphorylate SREBP-1. Recently, SREBP-1, which gets upregulated in different types of cancer, has been linked to play a role in the oncogenic signaling-mediated glucose uptake and de novo lipogenesis [46][47][48]. The pharmacological targeting of SREBP-1 has revealed to significantly inhibit the glioblastoma cell growth, suggesting it as a novel molecular target in cancer [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Zhao et al used a xenograft in a murine model to show that PKM2 is able to activate the nuclear transcription factor SREBP-1a, leading to cell proliferation and increased tumor progression. The interaction appears to be highly specific for this type of SREBP-1a (91, 92). This is an important result as it confirms the role of lipid accumulation in cancer progression.…”
Section: Metabolism Of Cancer Cells and Thyroid Hormones: Pkm2mentioning
confidence: 98%
“…Upon cholesterol depletion, the SCAP-SREBP complex moves to the trans-Golgi, where SREBPs are cleaved by the proteases S1P and S2P to allow for SREBP translocation from the Golgi complex to the nucleus, where they regulate the expression of lipogenesis-inducing genes and transporters. 151,152 Studies have shown important roles for SREBP function in T cells. Deletion of SCAP in T cells does not affect homeostatic proliferation, but impairs activation-induced cell growth, proliferation and differentiation, which promotes clearance of viral infections in vivo.…”
Section: Lipid and Cholesterol Synthesismentioning
confidence: 99%